Similar does not mean the same: ERP correlates of mental and physical experiencer verb processing in Malayalam complex constructions - Shalu, S.; Muralikrishnan, R.; Choudhary, Kamal Kumar (Frontiers in Human Neuroscience, 2025)
This study examined the neurophysiological correlates of processing mental experiencer verbs and physical experiencer verbs in Malayalam complex constructions, where the subject argument assumed the role of the experiencer. Event-related brain potentials (ERPs) were recorded as 28 first-language speakers of Malayalam read intransitive sentences with the two types of experiencer verbs. The subject case either matched (acceptable) or violated (unacceptable) the requirements of the verb in the critical stimuli. Both mental and physical experiencer verbs engendered negative effects in the 400–600-ms time window when the subject case did not match the verb’s requirements. Additionally, mental experiencer verbs evoked a left anterior negativity LAN-like effect in the same time window, regardless of grammaticality. Thus, even though both kinds of experiencer verbs are processed qualitatively similarly, inherent differences between mental and physical experiencer verbs in Malayalam persist and are discernible.